Observing electrochemical reactions on suspended graphene: an operando Kelvin probe force microscopy approach - Khatun, S; Cohen, SR; Peled, SS; Rosenhek‐Goldian, I; Weatherup, RS; Eren, B (Wiley, 2021)
An electrochemical micro-reactor sealed with a single-layer graphene (SLG) membrane is demonstrated that allows straightforward measurement with established scanning probe microscopies. SLG serves as a working electrode which separates the liquid electrochemical environment from the ambient to enable direct energy-level determination. Kelvin probe force microscopy (KPFM) thereby reveals the shifts in Fermi-level of suspended SLG under electrochemical reaction conditions in aqueous alkaline media. Polymer-free transfer to create suspended SLG minimizes contributions to doping related to any support or contaminants, such that changes in work function (WF) relate predominantly to the electrochemical system under study. These WF changes are rationalized in the context of a simple model of electrochemical gating, providing insight into the interplay between electronic and electrochemical doping (through redox of water) of suspended graphene. Further changes in WF are attributable to the reversible functionalization of graphene during the oxygen evolution reaction. Mechanical changes in the suspended graphene in the form of bulging also occur, which are attributed to electro-wetting of graphene induced by charge-carrier doping.